THE EFFECT OF BAYER STRATEGY IN DEVELOPING CRITICAL THINKING SKILLS FOR SECOND GRADE INTERMEDIATE STUDENTS IN ARABIC LANGUAGE - Raida Hussein Hamid; Ibtisam Sahib Mussa AL Zuwainy; Farman Qaht Rahima (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study was conducted at the University of Babylon / College of Basic Education and aims to identify (the impact of Bayer’s strategy in the development of critical thinking skills for second grade students in the Arabic language) and to achieve the goal of the research adopted the experimental approach as it included one variable (Bayer strategy) and a dependent variable (skills test The researchers adopted the experimental design with partial control to control the variables of research, and before starting the application of the experiment rewarded the two research groups to obtain accurate results, and prepared the research requirements and then studied the experimental group according to (Bayer strategy) and the group Duck (according to the (normal method) after the completion of the application of the experiment, and then the researchers applied a test of critical thinking skills as these data were treated statistically by the test (t-test) for two independent samples showed the results, the experimental group studied according to the Bayer strategy over the group The officer who studied in the usual way